Perbedaan Kemampuan Menulis Teks Eksplanasi Menggunakan Metode Cooperative Integrated Reading and Composition (CIRC) dengan Metode Konvensional Siswa Kelas VIII SMP Negeri 11 Kota Bengkulu - Emelia Julifa; Susetyo Susetyo; Rokhmat Basuki (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
The purpose of this study was to determine differences in writing ability using the Cooperative Integrated Reading And Composition (CIRC) method with conventional learning methods for Grade VIII students of SMP Negeri 11 Kota Bengkulu. This research method is quasi-experimental. The population in this study was class VIII SMPN 11 Kota Bengkulu, the sample in this study was class VIII C as the experimental class and class VIII D as the control class. The sampling technique used was purposive sampling technique. The data collection technique uses a test of the ability to write explanatory text. Based on the results of the study, there was a difference in the average value of the experimental class 81.8, while the average value of the control class using the conventional method was 76.6. The results of the difference test between the experimental group and the control group were tcount = 7.42 and ttable = 2.07 with a significant level of 0.05. The t test regarding students' ability to write explanatory texts showed a significant difference indicated by the value of tcount > ttable, namely 7.42 > 2.07 with a significant level of α = 0.05. Thus the null hypothesis is rejected and the alternative hypothesis is accepted, so that there are differences in the ability to write explanatory texts using the cooperative integrated reading and composition (CIRC) learning method with conventional learning methods for class VIII students of SMPN 11 Kota Bengkulu.